Adoption of Mobile Shopping in Finland and Germany: A Cross-Cultural Study - Lobin, Claudia (My University, 2013)
The rapid technological development revolutionized shopping in recent years and opened new possibilities for people to shop. So far only a limited amount of studies investigated factors that affect the adoption of mobile shopping; in particular in Western European countries. That is why this study investigates factors that predict the adoption of mobile shopping in Finland and Germany and how culture influences. The fundamental model TAM (perceived usefulness and perceived ease of use) is extended by perceived enjoyment, trust, innovativeness and subjective norm to investigate behavioral intention to adopt mobile shopping. The nature of the study is quantitative and the method applied is a survey questionnaire. The study was conducted in two universities and thus, the sample consists of students from these two universities. The impact of the determinants is tested through multiple linear regression analysis. Furthermore, the two countries are compared using Mann-Whitney U test. The effect of culture is investigated using multiple linear regression. Data analysis shows that the two countries differ in the factors considered important in the adoption of mobile shopping. German consumers are influenced by perceived usefulness, perceived enjoyment, trust and innovativeness in their decision to adopt mobile shopping, whereas perceived ease of use, perceived enjoyment, trust and subjective norm influence the decision of Finnish consumers. Furthermore, significant differences exist between four of the six factors. The two cultural dimensions have neither a moderating nor a direct effect on German respectively Finnish consumers' intention to adopt mobile shopping. This study extends the literature in the field of mobile shopping and contributes to cross-cultural research by comparing two countries and investigating two concrete cultural dimensions. Furthermore, it provides practical implications for companies and managers to increase the adoption rate of mobile shopping.
Keywords: Mobile Shopping; Culture; Finland; Germany; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|